PFI procurement skills: A cross-sector survey of practitioners - Zawawi, N.A.W.A. (Elsevier Ltd, 2014)
Contracting the private sector to construct and operate public infrastructure under the Private Finance initiative (PFI) has generated a lot of heated debate among practitioners. The debates derive their steam from increasing reports of failures which have bedeviled projects under these PFI arrangements. It has now become clear that there seems to be a general lack of adequate PFI contracting skills among public sector clients. The result is a lopsided risk transfer arrangement where the private sector privatizes profits and nationalizes losses. This study reports the results of a cross-sector survey attempting to investigate one of the most important issues raised in the now reformed PF2-public sector skills. It was found that stakeholder management, contract management, bid evaluation, risk management and regulatory governance skills were the most important overall. Though slight differences in ranking exist between the private and public sector but they tended not to be statistically significant. Â© 2014 The Authors. Published by Elsevier Ltd.